PENGARUH KELOMPOK ACUAN, RELIGIUSITAS, PROMOSI DAN PENGETAHUAN TENTANG LEMBAGA KEUANGAN SYARIAH TERHADAP MINAT MENABUNG DI KOPERASI JASA KEUANGAN SYARIAH (Studi Kasus pada BMT TAMZIS Wonosobo) - Kristiyadi Kristiyadi; Sri Hartiyah (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2017)
The development of the banking sector has grown Rapidly and dominate the Indonesian economy. The activities of the banking sector is very determine the progress of a state in the economy . Conventional banking system has in common with the Islamic banking system in terms of for- profit and community service in the financial business However , both have differences in terms of remuneration given system to its customers . To avoid the operation of the system of interest, born of Islamic banking in accordance with Islamic principles, namely the Cooperative Financial Services Sharia or often called BMT. BMT stands Baitul Maal wat Tamwil or Integrated Center for Independent Business. Baituttamwil, rather activity is to develop productive ventures and investment in improving the quality of economic activities of small entrepreneurs with, among others, to encourage the activities of saving and supporting economic activity (www.tamzis.com), and one of them is BMT TAMZIS in Wonosobo. The whole hypothesis in this study that states that the reference group, religiosity, and the promotion of knowledge has a positive influence on the interest of saving can be accepted. By hypothesis there is only one significant variable is knowledge, because of the relatively dominant significance and has the largest percentage of the interest savings in the amount of 19.3%. While variable reference group, religiosity and promotion does not contribute significantly to the variance in the interest of saving members BMT TAMZIS Baituttanwil. Results of regression testing showed koefien knowledge has the largest and has the smallest probability value of the variable variable knowledge lainnya.Dipengaruhi by 32.8%, and the remaining 67.2% is influenced by other variables not examined in this study. Keywords: influence of reference groups, religiosity, promotion, knowledge and interest in saving